Thienochrysenocarbazole‐Based Dyes for Solar Cell: A Theoretical Investigation of the Tethering‐Position‐Related Influence of Triple‐Bond on the Electronic and Optical Properties. Issue 41 (5th November 2018) - Mu, Yanfei; Dong, Guangxing; Dong, Xiandui; Zhang, Min
Abstract: The development of organic dyes based on polycyclic aromatic hydrocarbons (PAHs) donors characteristic of coplanar skeleton in conjunction with acceptors involving benzothiadiazole unit recently brought forth consecutive improvement for dye‐sensitized solar cells (DSCs). In this paper, we systematically investigate the tethering‐position‐related influence of triple‐bond insertion on the intrinsic geometric, electronic and optical properties of organic dyes with PAHs as the central blocks based on the density functional theory. We consider two isomer donors, where a thienochrysenocarbazole (TCC) unit is substituted by alkoxyphenyl at either thiophene ( t ‐PTCC) or naphthalene ( n ‐PTCC) moiety, with benzothiadiazole‐benzoic acid acceptor linked to the donor either directly or through ethynyl linkage. The tethering‐position‐related torsion angle between the donor and acceptor plays a significant role in determining the electronic and optical properties of these sensitizers. The introduction of triple‐bond can bring forth improved coplanarity of skeleton as well as energy‐gap shrinkage; however, it also results in an increased distance between the spatial distributions of the frontier molecular orbitals. Our study has underlined that the resultant red or blue shifting of absorption spectrum induced by the triple‐bond insertion is jointly determined by the interplay between the overlap degree of frontier molecular orbitals and energy‐gap. Abstract : We have systematically investigated the influence of triple‐bond insertion on the intrinsic geometric, electronic and optical properties of organic dyes with PAHs as the central blocks at the density functional theory level. The introduction of triple‐bond can bring forth improved coplanarity of skeleton as well as energy‐gap shrinkage; however, it also results in an increased distance between the spatial distributions of the frontier molecular orbitals.